Antibacterial activity and phytochemical screening of Kesambi (Sapindaceae) against Eschericia coli and Staphylococcus aureus - Boima Situmeang; Agus Malik Ibrahim; Nurhayati Bialangi; Weny J.A Musa; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2019)
Kesambi plant (Schleichera oleosa) is a medicinal plant belongs to family Sapindaceae, commonly found in tropical and subtropical regions of the world. In Indonesia, kesambi plants can be found in Java and Bali island. The purpose of this study is to extraction and antibacterial activity test of steam bark extract of kesambi against Escherichia coli and Staphylococcus aureus. Extraction was done by maceration method using n-hexane, ethyl acetate and methanol. Antibacerial test using Kirby bauer method by measure inhibition zone. Phytochemical screening shown that n-hexane extract contain triterpenes and steroid compounds. Ethyl acetate extract contain triterpenes, flavonoid, steroid, and fenolic compounds. Methanol extract contain flavonoid, fenolic and triterpenes compounds. Inhibition zone of n-hexane, ethyl acetate and methanol extracts against E. coli and S. aureus at concentration of 5000 µg/mL showed 4.4; 7.9; 4.6 mm and 4.7; 8.9; 4.5 respectively, while amoxicillin and ciprofloxacin as positive control at concentration of 100 µg/mL showed 6.9 and 7.1 mm respectively. Kesambi extract have potential as antibacterial against E. coli and S. aureus.Keywords:Kesambi; antibacterial; Eschericia coli; Staphylococus aureus